A Prospective Comparative Study of the Outcome of Double-Y Pyloromyotomy (Alayet's Pyloromyotomy) and Ramstedt's Pyloromyotomy for the Surgical Management of Infantile Hypertrophic Pyloric Stenosis (Journal of Paediatric Surgeons of Bangladesh, 2014)
Background: Many innovations and approaches have been tried for the surgical management of Infantile Hypertrophic Pyloric Stenosis (IHPS) since Ramstedts first successful surgery almost one hundred years ago. Here a new technique focusing on the pylorus which may offer better results for this common condition.Methods: A prospective on going study of 20 patients with IHPS are carried out over a period of 15 months from July 2008 to September 2009. The patients are divided into 2 equal groups of 10 patients in each. The study is designed that all patients selected for study are optimized preoperatively with regard to hydration, acid-base status and electrolytes imbalance. All surgeries are performed after obtaining informed consent. Standard preoperative preparation and postoperative feeding regimes are used. The patients are operated on an alternate basis, i.e., one patient by double-Y pyloromyotomy(DY) and the next by a Ramstedts pyloromyotomy(RP). Data on patient demographics, operative time, anesthesia complications, Postoperative complications including vomiting and weight gain are collected. Patients are followed up for a period of 3 months postoperatively. Statistical assessments are done by using Student test.Results: No statistical differences are observed in patient population regarding age, sex, weight at presentation, symptoms and clinical condition including electrolytes imbalance and acid-base status. Significant differences are found in postoperative vomiting and weight gain. Data of post operative vomiting and weight gain in both groups are collected. Vomiting in double- Y(DY) pyloromyotomy group (1.23 ± 0.98 days) vsRamstedts pyloromyotomy (RP) group(2.950.99 days) p= 0.0094.Weight gain after 1st 10 days DY vs RP is ( 298 ± 57.94 gm vs193±19.8 gm p=0.0014), after 1 month (685±15.72 gm vs 498 ± 12.36 gm, p=0.0008), after 2months (670± 105.93 gm vs 455±79.76 gm, p=0.00013) and after 3 months (555±86.44 gm vs 435±47.43 gm, p=0.00098).No long-term complications are reported and no re-do pyloromyotomy is needed.Conclusion: The double-Y pyloromyotomy seems to be a better technique for the surgical management of IHPS. It may offer a better functional outcome in term of postoperative vomiting and weight gain.DOI: http://dx.doi.org/10.3329/jpsb.v1i1.19449